PENGARUH MOTIVASI KUALITAS, MOTIVASI KARIR, MOTIVASI EKONOMI DAN MOTIVASI SOSIAL TERHADAP MINAT BERKARIR DALAM BIDANG PERPAJAKAN (Studi Kasus Pada Universitas Sarjanawiyata Tamansiswa) - Fajar Setiya Nuggrahini; Andri Waskita Aji; Anita Primastiwi (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2022)
This study aims to determine the effect of quality motivation, career motivation, economic motivation, and social motivation on career interest in taxation. This study uses quantitative methods, the data used are primary data and data collection techniques using a questionnaire changed Google form. The sample in this study were students of the accounting study program, Faculty of Economics, University of Sarjanawiyata Tamansiswa. Sampling was carried out using the Snowball sampling technique. Data processing was processed using the help of the IBM SPSS version 20 program as many as 95 respondents. The results of this study indicate that quality motivation affects career interest in taxation, career motivation does not affect career interest in taxation, economic motivation does not affect career interest in taxation, and social motivation affects career interest in taxation